Unsettling Thought An Alternative to Sedentary Concepts and a Defence of Frodo (Existential Analysis: Journal of the Society for Existential Analysis, 2007)
In the last issue of Existential Analysis, Helen Hayes offers an interesting exploration of 'migration, settlement and the meanings of home' (2007: 2-16). Her paper provides a much-needed additional perspective to the ideas offered in my own article 'Existential Migration' (Madison, 2006). Hayes' references to my paper demonstrate the need for further elaboration and clarification in my original article and I take the opportunity here to offer some of that. I also want to suggest that there is a conventional settled-centric bias inherent in our understanding of migration but more so, to suggest that our thinking in general is too 'settled'. I propose that it might be valuable to develop thinking based upon an alternative migratory use of concepts: unsettled thinking.
Keywords: Home; migration; existential; phenomenological; cross-cultural; Heidegger; conceptual development; alienation; belonging; unheimlich; acculturation.